2017
DOI: 10.1002/2016jc012654
|View full text |Cite
|
Sign up to set email alerts
|

Impact of wave breaking on upper-ocean turbulence

Abstract: Previous studies have demonstrated that surface wave breaking can impact upper‐ocean turbulence through wave‐breaking‐induced turbulence kinetic energy (TKE) flux and momentum flux. Wave‐breaking‐induced momentum flux decays approximately exponentially with depth, and the decay exponent depends on both the wind speed and wave age. With increasing wave age, the decay speed of wave‐breaking‐induced momentum flux first decreases, reaching a minimum around a wave age of 16, and then increases. In this study, a wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(138 reference statements)
0
2
0
Order By: Relevance
“…The wave-induced turbulent kinetic energy (TKE) flux is usually parameterised in terms of a friction velocity (Craig and Banner, 1994). The parameterization works relatively well for fully developed sea state but performs poorly under growing and decaying sea states (Kantha and Clayson, 2004;He and Chen, 2011;Cai et al, 2017).…”
Section: The Wave-induced Energy Flux and Turbulencementioning
confidence: 99%
“…The wave-induced turbulent kinetic energy (TKE) flux is usually parameterised in terms of a friction velocity (Craig and Banner, 1994). The parameterization works relatively well for fully developed sea state but performs poorly under growing and decaying sea states (Kantha and Clayson, 2004;He and Chen, 2011;Cai et al, 2017).…”
Section: The Wave-induced Energy Flux and Turbulencementioning
confidence: 99%
“…Jenkins et al (2012) observed that the waves act as roughness elements in MABL, affecting the turbulent flow and the vertical wind speed profile as well as inducing oscillatory motions in the atmospheric flow. Moreover, atmosphere-ocean wave interaction affects the mixing of heat and momentum in the upper ocean layers (Sullivan and Williams, 2010;D'Asaro et al, 2014;Breivik et al, 2015;Wu et al, 2015;Alari et al, 2016;Ličer et al, 2016;Staneva et al, 2016;Aijaz et al, 2017;Cai et al, 2017) and the ocean circulation (e.g. Burgers et al, 1995;Clementi et al, 2013;Turuncoglu et al, 2013;Fan and Griffies, 2014;Kim et al, 2014;Carniel et al, 2016).…”
Section: The Role Of Ocean Waves On Air-sea Interactionmentioning
confidence: 99%